2014
DOI: 10.1016/j.jtcvs.2013.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Obesity paradox in coronary artery bypass grafting: Myth or reality?

Abstract: Obesity did not increase operative mortality, but it was associated with reduced late survival in patients undergoing primary isolated CABG. Our results raise concerns in supporting any protective effect of obesity in cardiovascular disease, specifically in patients undergoing surgical myocardial revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 16 publications
1
43
2
3
Order By: Relevance
“…The term ‘obesity paradox’ explains a protective role of high BMI in patients with coronary artery disease, because of better early and long-term outcomes compared to patients with a low BMI (1415). However, our findings revealed a statistically significant inclination for increased in-hospital mortality with decreasing BMI values (15). Our study revealed that BMI had no impact on postoperative AF.…”
Section: Discussionmentioning
confidence: 99%
“…The term ‘obesity paradox’ explains a protective role of high BMI in patients with coronary artery disease, because of better early and long-term outcomes compared to patients with a low BMI (1415). However, our findings revealed a statistically significant inclination for increased in-hospital mortality with decreasing BMI values (15). Our study revealed that BMI had no impact on postoperative AF.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these limitations, it is difficult to conclusively determine the association between BMI and perioperative mortality. Compared with normal weight patients, at this time the literature suggests a survival benefit in the lower BMI obesity range and worse long-term mortality at the higher BMI ranges (>40 kg/m 2 ) [41,42,44].…”
Section: Mortalitymentioning
confidence: 85%
“…Though some surgical literature suggest that any increase in BMI over normal is associated with decreased survival [5,41], other surgical literature suggest an obesity paradox, where limited increases in BMI (in the 25-40 kg/m 2 range) may provide a survival benefit compared with normal weight patients [6 && ,42-44]. Analysis of ACS-NSQIP data on cardiovascular, orthopedic, and oncologic surgeries indicate that patients with BMI at least 25 kg/m 2 did not have an increased odds of 30-day mortality, and in fact those with BMI 25-40 kg/m 2 experienced significantly lower odds of 30-day mortality following abdominal aortic aneurysm repair, total hip arthroplasty, gastrectomy, and colectomy [6 && ].…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations